Iklim Panti Asuhan, Self Concept dan Motivasi Melanjutkan Studi Remaja Panti Asuhan ke Universitas - Rahmah Saniatuzzulfa; Tanri Fatma Utami (Jurnal Ilmu Perilaku, 2022)
The purpose of this research was to determine the contribution of the orphanage climate and self-concept to motivation in orphanage youth Muhammadiyah Purworejo to continue their studies to collage. Research respondent totaled 81 people selected using cluster random sampling. The scale used for data collection include the Motivation Scale for Continuing Studies in University (α=0,930), the Orphanage Climate Scale (α = 0.862), and the Self-Concept Scale (α=0,870). The results of the regression analysis showed that there was a strong contribution between the climate of the orphanage and self-concept to the motivation in orphanage youth Muhammadiyah Purworejo to continue studying at university (Fcount>Ftable, namely 53,151>3,11; p<0,05; R=0,759). In addition, the pearson correlation test of the second and third hypotheses of this study proved to show a strong enough significant correlation between the climate of the orphanage and the motivation in orphanage youth Muhammadiyah Purworejo to continue their studies to collage (p<0,05, r=0,423) and there was a strong significant correlation between self-concept and motivation in orphanage youth Muhammadiyah Purworejo to continue study in higher education (p<0.05; r=0,756). The effective contribution of the orphanage climate and self-concept to the motivation in orphanage youth Muhammadiyah Purworejo to continue their studies to college is 57,7%.